Rekonstruksi Konsep Manajemen Biaya Dalam Pendidikan Islam: Analisis Efisiensi, Transparansi, Dan Nilai Syariah - Ahmad Fauzan; Rahayu Utami, Dwi; Noviarita, Heni; Romlah (Kartika: Jurnal Studi Keislaman, 2025)
Cost management in Islamic education plays a pivotal role in ensuring the sustainability and quality of educational services. In the current era of globalization and digital transformation, Islamic educational institutions face a range of challenges, including limited funding, unequal access to education, inefficient budgeting, and the lack of digital financial systems. These issues demand a reconstruction of cost management concepts that not only emphasize efficiency but also incorporate transparency and Islamic ethical principles. This article aims to develop a conceptual model of cost management in Islamic education through a literature study by analyzing various theories of educational economics, funding practices, and case studies from Islamic institutions across Indonesia. The findings indicate that an integrative approach based on sharia principles, digitalization of financial systems, and the utilization of alternative funding sources such as productive waqf and corporate social responsibility (CSR)—offers a strategic and sustainable solution. This study also highlights the importance of strengthening human resource capacity in financial management and fostering institutional collaboration to optimize resource use. Therefore, reforming the financial management system grounded in Islamic values is a strategic step toward creating inclusive, high-quality, and competitive Islamic education in the modern era.